Ultrasound Assisted Extraction and Characterization of Pectin from Red Dragon Fruit (Hylocereus Polyrhizus) Peels - Triana Lindriati; Maria Belgis; Mukhamad Fauzi; Qriyasa Etik Juwita; Sakinah Sakinah (Journal of Applied Agricultural Science and Technology, 2023)
Pectin has numerous applications in the food industry because of its gelling capability. Dragon fruit peel is an ideal source of pectin since it contains pectin of around ± 10.8% of the weight. In this research, the extraction of pectin from dragon fruit peels used ultrasonic waves. This study was an experimental research with three independent variables that was a type of acid (HCl and CH3COOH), acid concentration (0.1 N and 0.2 N), and extraction time (30, 60, and 90 minutes). The control sample was pectin extracted by conventional methods, dipped in 0.1 N acids at room temperature for 24 hours. The result showed that the ultrasound-assisted extraction was an effective method to extract pectin from peels of red dragon fruits, whereas the yield was even twice that compared with the control sample. The treatment of 90 minutes of sonication in 0.2 N HCl produced the highest yield (2.71%). The pectin has a yellowish to a white degree of color and a 2.22 g.s/cm viscosity. It has a 902.2 mg equivalent weight, 6.14% methoxyl content, 54.4% galacturonic acid content and 63.8% esterification degree. The value of esterification degree and methoxyl content indicated that pectin from this research is high ester-pectin and low-methoxyl pectin.